Investing in the hydrogen delivery infrastructure: methodology for a public policy - Bento, N. (Energy Studies Review, 2010)
Hydrogen and fuel cells are a radical innovation with great potential, but they are currently surrounded by numerous uncertainties. It is argued that demand and technological uncertainties are particularly important. An economic analysis is performed for a hydrogen refuelling station to understand the way uncertainties work. Even though the investment has a negative NPV today, it can be justified by the option value given to the owner for the future. In addition, the profitability of the station depends heavily on the demand; the evolution of which is still unpredictable unless public authorities decide to create a stable early demand.